PENGARUH KINERJA KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Sinaga, Hermika Juita Sinaga; Wangdra, Ronald (LPPM Universitas Putera Batam, 2022)
This study aims to determine the effect of profitability ratios, liquidity ratios, and solvency ratios on profit growth in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The variables in this study are net profit margin (NPM), return on assets (ROA), current ratio (CR), debt to asset ratio (DAR). The population used in this study is the food and beverage sub-sector of manufacturing companies on the Indonesia Stock Exchange for the period of 2021. The source of the data is obtained from the financial statements of companies listed on the IDX. The sampling technique in this study used purposive sampling technique, so that 55 company data were obtained. The data analysis technique was carried out by multiple linear regression analysis with the help of SPSS version 28. The results of the T test analysis showed that partially return on assets had a significant effect on profit growth, while net profit margin, current ratio, and debt to asset ratio had no effect on profit growth. Simultaneously return on assets, net profit margin, current ratio, and debt to asset ratio have a significant effect on profit growth in manufacturing companies on the IDX in 2021.